THE EMOTIONS IN THE EDUCATIONAL CONTEXT AND QUALITY ASSESSMENT OF ONGOING PLATFORMS FOR ONLINE TEACHING ON THE TERRITORY OF KOSOVO AND METOHIJA (Heritage, 2021)
The theoretical basis of the work is represented by the theory of control and value of emotions and Pekurn's understanding of academic emotions as well. The main goal of the research was to examine the expression of positive emotions such as enjoyment, pride, relaxation or relief and  negative emotions as well, such as anger, boredom, anxiety at students during online classes, as well as their relationship to overall success and quality assessment of online teaching platforms in use.The following material was used in this work: Achievement Emotion Questionnaire (AEQ), Questionnaire on Quality Assessment of ongoing Online Teaching Platforms (UPKPON1) and Questionnaire of Sociodemographic Variables.  A hundred high school final year students from Kosovo and Metohija were involved in this sample. The results showed that during online classes positive emotions such as enjoyment, pride and relief are experienced more intensely than negative ones such as anger, anxiety and boredom;  the most expressed positive emotion is enjoyment, and the most expressed negative emotion is boredom. Experience of positive and negative emotions during online teaching doesn’t correlate significantly with students' school success.  The most of students were using laptops to monitor online classes and they had adequate internet speeds as well as their own device for monitoring classes. Students expressed a neutral general attitude towards online teaching; Google Meet platform was the most used platform to follow online classes. A significant correlation between the experience of positive and negative emotions and the general attitude towards online teaching was proved. The students who felt more anxious, angry and got bored during online classes expressed more satisfaction with online classes. There is a difference in the expression of certain positive and negative emotions during online classes with regard to the gender and type of high school that students attend.
Keywords: high school students, academic emotions, online teaching, the quality assessment of platforms, Kosovo and Metohija